Exposure to microplastics in the upper respiratory tract of indoor and outdoor workers. (November 2022) - Jiang, Ying; Han, Jinchi; Na, Jun; Fang, Jing; Qi, Chanchan; Lu, Junge; Liu, Xiaojing; Zhou, Changhe; Feng, Jing; Zhu, Weiwei; Liu, Li; Jiang, He; et al.
Abstract: The aim of this study was to determine the presence of microplastics (MPs) in the upper respiratory tract of indoor and outdoor workers, to assess the type and the extent of contamination. Sputum and nasal lavage fluid were collected, and plastic particles were quantitatively analyzed by polarizing microscopy and a laser direct infrared chemical imaging system. The polarized light microscopy results showed that suspicious MPs were found in the nasal lavage and sputum of both couriers and office staff, and the abundance of MPs in the nasal lavage of office staff was significantly higher than in couriers ( P  < 0.0001). The chemical imaging results showed that polycarbonate (24.2%) and polyvinylchloride (PVC) (23.0%) were the predominant plastic materials in the sputum of couriers, while polyamide (PA) (25.3%) and polyethylene (22.9%) were dominant in the nasal lavage fluid. The sputum and nasal lavage fluid of office staff were both dominated by PVC (39.1% and 41.1%, respectively) and PA (24.8% and 31.6%, respectively). Therefore, this study revealed that microplastic pollution was found in the respiratory tract of both indoor and outdoor workers, but the distribution of MP particles differed between the two populations. Graphical abstract: Image 1 Highlights: Microplastic pollution was detected in the upper respiratory tract of humans. Microplastic particle abundance differed between indoor and outdoor workers. Microplastic exposure of indoor and outdoor workers was dominated by microplastic fibers.